Bibliometric Analysis on Covid-19 Research Publications - Athanasia Octaviani Puspita Dewi (Diponegoro University, 2025)
The variety of research topics will develop along with the development of science and conditions experienced by society. In the beginning, it was unpredictable that COVID-19 would paralyze many human activities. This also has an impact on science, this epidemic provides a new discourse in conducting research. Due to the emergence of the COVID-19 pandemic, a lot of research has turned its focus on this topic. This study aims to map research that discusses COVID-19 in Indonesia which is indexed by Scopus. The results of this study indicate that many studies in Indonesia discuss online learning that occurred during the COVID-19 pandemic.